Innovation Trends: Untilization of Social Media and Interective Video in Leprosy-Related Health Promotion - Ardia, Aulia Gayo Dwi; Hutami, Citra Kirana; Sucita, Ni Made Dwiastini (Tarqabin Nusantara Group, 2024)
Leprosy is an infectious disease caused by Mycobacterium Leprae. This disease has become a health problem in several countries, one of which is Indonesia. The impact of leprosy is physical, economic and psychological disability. Health promotion is an effort by individuals and communities to increase their abilities in several factors that influence health so that they can improve their health. Health promotion activities regarding leprosy are carried out by making videos regarding education the prevention of leprosy using promotional media in the form of Instagram. The method used is qualitative content analysis from educational videos related to leprosy which are posted on the Instagram page @komkes.ikmb.22. There are 2 processes in this activity: 1) formulation of material and content ideas related to leprosy prevention; and 2) creating leprosy health promotion media. Leprosy education using social media can be done by disseminating accurate and educative information about leprosy through social media platforms and not causing discrimination against leprosy sufferers. Instagram can be used as a means of health promotion and health communication tool to fight leprosy. Instagram is effective medium, because it is widely used and has a large number of active users. The Indonesian Ministry of Health stated that there are still a number of challenges in eliminating leprosy cases in Indonesia. Therefore, an effective solution is needed to overcome this. Through social media, especially Instagram, it is hoped that efforts to deal with leprosy in society will become more systematic, comprehensive and effective